6th AIAA Atmospheric and Space Environments Conference 2014
DOI: 10.2514/6.2014-2751
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Sensor for Total Temperature and Humidity Measurements under Mixed-Phase and Glaciated Icing Conditions

Abstract: This paper presents a critical development to a prototype sensor that is capable of measuring total air temperature and humidity in a mixed-phase environment, consisting of liquid water droplets and ice crystals. The sensor has fast and stable measurement response under particularly challenging mixed-phase conditions. Total temperature and humidity levels measured with the probe are in good agreement with the results of analytical energy and moisture balances. NomenclatureC p = Specific heat capacity E = Energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…A gas velocity at the tunnel exit of ve = 85 m/s was specified as a model parameter input. Liquid water was injected with an initial temperature of 280.4 K (45 °F) at a bulk total water content of TWCbulk = 2.26 g/m 3 . The value of TWCbulk was calculated as the ratio of water mass flow rate to volumetric gas flow rate at the test section and is calculated using Eq.…”
Section: Model Sample Resultsmentioning
confidence: 99%
“…A gas velocity at the tunnel exit of ve = 85 m/s was specified as a model parameter input. Liquid water was injected with an initial temperature of 280.4 K (45 °F) at a bulk total water content of TWCbulk = 2.26 g/m 3 . The value of TWCbulk was calculated as the ratio of water mass flow rate to volumetric gas flow rate at the test section and is calculated using Eq.…”
Section: Model Sample Resultsmentioning
confidence: 99%
“…Increases from the other energy sources mentioned have been estimated for runs at the ends of the plateau in Fig. 23 using T o , ω measured under wet conditions 19 and a stagnation point heat transfer coefficient obtained from the correlation of Kestin and Wood 20 with the measured tunnel turbulence intensity of 7.75% 4 . The impinging water droplet temperature was assumed to equal the wet value of T wb , and changes in the sensible heat of the ice crystals between M=0.25 and M=0.4 were ignored.…”
Section: Effect Of Pressurementioning
confidence: 99%
“…More details on the TAT & RH probe can be found elsewhere. 8 When the cloud is activated, a temperature change (T) and humidity change is typically measured by the TAT & RH probe. That T is applied to the dry (cloud off) measurement from P0 & T0 probe to establish the total temperature at the test section with the cloud on, T0,on.…”
Section: Aerothermal Measurementsmentioning
confidence: 99%
“…During all the previous testing, air temperature and humidity measurements showed changes at the test section when the cloud was active compared to when the cloud was off. The most recent joint NASA and NRC test 7 in March 2012 included a traversable total air temperature (TAT) & relative humidity (RH) probe 8 which allowed measurements at tunnel centerline. Subsequent modelling showed that a decreasing air temperature was due to the energy exchange from the partial evaporation of the cloud [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%